Absence of tmRNA Increases the Persistence to Cefotaxime and the Intercellular Accumulation of Metabolite GlcNAc in Aeromonas veronii - Yu, Wenjing; Li, Daiyu; Li, Hong; Tang, Yanqiong; Tang, Hongqian; Ma, Xiang; Liu, Zhu (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial persisters are a small proportion of phenotypically heterogeneous variants with the transient capability to survive in high concentrations of antibiotics, causing recurrent infections in both human and aquatic animals. Transfer-messenger RNA (tmRNA), which was encoded by the ssrA gene, was identified as a determinant regulator mediating the persistence to β-lactams in the pathogenic Aeromonas veronii C4. The deletion of tmRNA exhibited the increased ability of persister formation most probably due to the reduction of protein synthesis. Transcriptomic and metabolomic analyses revealed that the absence of tmRNA not only significantly elevated the intercellular levels of metabolite GlcNAc and promoted NaCl osmotic tolerance, but also upregulated the expression of metabolic genes in both the upstream biosynthesis pathway and the downstream metabolic flux of peptidoglycan (PG) biosynthesis. Finally, exogenous GlcNAc stimulated significant bacterial growth, enhanced content of GlcNAc in the cell wall, higher resistance to osmotic response, and higher persistence to cefotaxime in a concentration-dependent manner, implying its potential role in promoting the multiple phenotypes observed in tmRNA deletion strains. Taken together, these results hint at a potential mechanism of persister formation mediated by tmRNA against the β-lactam challenges in A. veronii.